Fatting parameters after duck egg exposure to γ-radiation - Dvořák, P; Doležalová, J; Suchý, P; Straková, E; Zapletal, D; Rulík, V (Poultry science, 2019)
In our experiment, we deal with the phenomenon of radiation hormesis and improvements based on this phenomenon to different growing characteristics of the fast-growing, very feed-efficient, and with a high-yielding carcass hybrid of the Peking duck (Cherry Valley SM3 medium). In the first phase of the project, we exposed hatching duck eggs to low and middle doses of gamma radiation 60Co (0.06-2.00 Gy) before placing them into a setter in the hatchery. We then followed the standards of artificial incubation. The treatment of our chosen doses of gamma radiation has no significant influence on the history and results of hatching (from 85.5% to 92.6%); it was influenced only by the basic management and husbandry of the parent stock. From our observations we confirm that the Peking duck, despite genetic progress, retained its vitality and robustness. Its embryos are not damaged even with a dose of 2 Gy, which is over the deterministic effect of ionizing radiation for vertebrates. At the end of the fatting period a significant drop in plasma phosphorus levels was measured in the ducks; however, it was dependent on the radiation dose to which the hatching eggs were exposed (r = -0.965). A positive effect of radiation hormesis may be expected in the case of 1 Gy dose where the highest values of mean corpuscular hemoglobin, mean corpuscular hemoglobin, combined hemoglobin, and drake weight were measured. Lower and higher doses of ionizing radiation used did not display these effects.
Keywords: záření gama; Animals; hormeze; rozmnožování; kachny; Gamma Rays; radioizotopy kobaltu; Ducks; Hormesis; Reproduction; Cobalt Radioisotopes; ovum; hormesis; duck; Random Allocation; Ovum; zvířata; vztah dávky záření a odpovědi; náhodné rozdělení; low-dose radiation; Dose-Response Relationship, Radiation